Bone biology and the pathogenesis of osteoporosis. - Russell, R; Espina, B; Hulley, P (2006)
Much is now known about skeletal biology and the changes that take place during diseases. Skeletal development is programmed by the sequential activation of specific genetic pathways that culminate in the production of the adult skeleton, which is light but strong. Systemic hormones including parathyroid hormone, vitamin D metabolites, and calcitonin regulate blood calcium levels and contribute to the overall calcium economy of the body. Many other hormones have subtle but important effects on skeletal behaviour and its modelling and remodelling activity. At a local level, the integration of cellular differentiation and function within the microenvironment of bone is under the influence of a large number of cytokines and growth factors. Osteoporosis is a very common disorder and is a result of perturbation in these regulatory mechanisms. Much has been learnt in recent years about the many pathogenic processes that contribute to bone loss and fragility. Several drug treatments are now available to prevent bone loss and reduce the incidence of fractures, and there are prospects for the development of further novel pharmacological interventions that may modify some of the pathogenic processes themselves. Among the newer pathways for pharmacological intervention, the calcium-sensing receptor and the receptor activator of nuclear factor kappa B ligand/receptor activator of nuclear factor kappa B/osteoprotegerin system involved in osteoblast-osteoclast interactions offer exciting opportunities.